Hubungan Pola Asuh Orang Tua dengan Perkembangan Anak Usia Prasekolah di TK RA Cut Nyak Dien - Ketjuk Herminaju; Ratna Kholidati (Pediomaternal Nursing Journal, 2019)
Introduction: Development is a progressive which means irreversible, development that is movement, language, social and independence. The age of preschoolers can be ordered as a golden period or golden age, an important period in development. In this period parents' parenting is very important. But parents sometimes do not pay attention to parenting who is good, they are always worried about what if left alone. Therefore parents must know the importance of having good parenting. The purpose of this study was to study the pattern of foster care of parents with the development of preschool children.Methods: Pre correlational with cross sectional method. Population of all parents and preschoolers at RA Kindergarten. Cut Nyak Dien in Gendingan Kedungwaru Village for 6 - 08 February 2018 as many as 72. The samples of this study were 72 parents and preschool children who met the inclusion and exclusion criteria. Total sampling technique, questionnaire and KPSP instruments, and spearman rank ranking statistics ( rho) with α = 0.05.Results: The study obtained 63 (87.5%) parents who had authoritative parenting and with appropriate child development as many as 65 (90.3%) while authoritarian parenting with a number of 1 (1.4%). spearman rank (rho) with a value of P = 0,000 <α (0,05), then there is a relationship between Parenting Parenting and the Development of Preschool children in TK RA. Cut Nyak Dien Gendingan village Kedungwaru.Conclusion: Parenting Parenting has a relationship to the development of preschool children. Where parents who have authoritative parenting, the development of children in accordance with the development.